2009
DOI: 10.1002/cne.21950
|View full text |Cite
|
Sign up to set email alerts
|

Regressive events in rat corticospinal axons during development in in vitro slice cocultures: Retraction, amputation, and degeneration

Abstract: Axonal regression is utilized to refine neuronal circuits during development, but the dynamic properties of such regression remain largely unknown. We used confocal time-lapse imaging to examine the regression of single enhanced yellow fluorescent protein-labeled axons in corticospinal slice cocultures. By acquiring images at long (1 day) and short (30-60 min) intervals on days 5-13 in vitro, we detected three types of regressive events: 1) retractions, 2) amputations (referred to as autoaxotomy), and 3) degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Several studies have shown that almost none of the ectopic axons enters the spinal gray matter (Joosten et al, 1987;Oudega et al, 1994). On the other hand, in the previous studies of the development of CS projections in rodents, we found that CS axons initially form synapses throughout the spinal gray matter (Ohno et al, 2004;Kamiyama et al, 2006;Maeda et al, 2007;Yoshioka et al, 2009), but those on the ventral side are largely eliminated in an NMDAand GluN2B-dependent manner (Ohno et al, 2010). Many of these observations were made in vitro, however.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Several studies have shown that almost none of the ectopic axons enters the spinal gray matter (Joosten et al, 1987;Oudega et al, 1994). On the other hand, in the previous studies of the development of CS projections in rodents, we found that CS axons initially form synapses throughout the spinal gray matter (Ohno et al, 2004;Kamiyama et al, 2006;Maeda et al, 2007;Yoshioka et al, 2009), but those on the ventral side are largely eliminated in an NMDAand GluN2B-dependent manner (Ohno et al, 2010). Many of these observations were made in vitro, however.…”
Section: Introductionmentioning
confidence: 53%
“…9B). Despite a shorter expression time than usually used in optogenetic experiments (Zhang et al, 2010), YFP immunoreactivity was widely discernible in the spinal gray matter, suggesting that ChR2-EYFP was expressed at considerable levels within 1 week and was transported to the distal portion of CS axons (Fig. 9C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the bilaterally projecting axons observed in our study might be a temporary compensatory system and could be eliminated after a certain period. Previous studies of normal rats reported that corticospinal synapses were widely formed in the spinal gray matter at P7, and rapidly eliminated from the ventrolateral side, indicating that the decrease in the number of synapses on the ventral side is due primarily to axon branch elimination rather than to cortical neuron death [37,38,39]. The elimination of axon branches found in normally developing rats might also occur in neonatal rats with unilateral brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies have also indicated that corticospinal axon temporarily project over all gray matter in the spinal cord, but superfluous axons existing in the ventral gray matter are eliminated with growth [ 19 ]. This axonal elimination has been demonstrated by slice co-culture [ 20 ]. Although not much has been done on the molecular aspects of brain injury in context of motor function, molecular mechanisms of axon guidance in the developing CST have been reported.…”
Section: Introductionmentioning
confidence: 75%